2018
DOI: 10.1103/physrevb.97.064409
|View full text |Cite
|
Sign up to set email alerts
|

Coherent spin dynamics of ytterbium ions in yttrium orthosilicate

Abstract: We investigate the electron and nuclear spin coherence properties of ytterbium (Yb 3+ ) ions with non-zero nuclear spin, within an yttrium orthosilicate (Y2SiO5) crystal, with a view to their potential application in quantum memories or repeaters. We find electron spin-lattice relaxation times are maximised at low magnetic field (< 100 mT) where g ∼ 6, reaching 5 s at 2.5 K, while coherence times are maximised when addressing ESR transitions at higher fields where g ∼ 0.7 where a Hahn echo measurement yields T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 62 publications
3
42
0
Order By: Relevance
“…Since flip-flop interactions do not change the overall level populations, the recovery rate R c , obtained by an exponential fit to the data, corresponds to the SLR rate. This result is confirmed by the R c temperature dependence, which can be well modeled by a sum of a direct process and two-phonon processes, with parameters consistent with previous studies at higher magnetic field [33], as detailed in the Supplemental Material [38]…”
Section: (B)supporting
confidence: 88%
See 2 more Smart Citations
“…Since flip-flop interactions do not change the overall level populations, the recovery rate R c , obtained by an exponential fit to the data, corresponds to the SLR rate. This result is confirmed by the R c temperature dependence, which can be well modeled by a sum of a direct process and two-phonon processes, with parameters consistent with previous studies at higher magnetic field [33], as detailed in the Supplemental Material [38]…”
Section: (B)supporting
confidence: 88%
“…We next investigate optical coherence lifetimes T 2;o under DEOP. This investigation was motivated by several studies that have shown that flipping ground-state spins of paramagnetic RE can be a major source of magnetic noise and therefore cause dephasing to RE optical and spin transitions [8,33]. This dephasing can be reduced by inducing strong spin polarization under large magnetic field and/or ultralow temperatures, by broadband optical pumping, or by using excited-state spins [13,14,30,42,43].…”
Section: B Optical Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…2e) to the intrinsic spin dynamics of the sample. We might also argue that the different efficiency of CP and DD sequences is due to the fact they address different spectral portions of the environmental noise distribution 36,38,42 . However, a more detailed analysis of this latter point would require a dedicated work.…”
Section: Dynamical Decoupling Sequencesmentioning
confidence: 99%
“…These protocols are widely used to dynamically decouple the spins from environmental sources of decoherence and, hence, are expected to enhance T m [36][37][38][39] . Although the efficiency of CP and DD sequences has been previously investigated on spin impurities in inorganic matrices [40][41][42] and in organic molecules [43][44][45] (including radicals 39,46 ) coupled to conventional (3-dimensional) ESR cavities, their efficiency still needs to be tested on molecular spins in working conditions 1,21 . Here we report, for the first time to the best of our knowledge, an extensive study concerning the PW manipulation of molecular spins embedded into planar resonators.…”
Section: Introductionmentioning
confidence: 99%